2001
DOI: 10.1097/00002030-200111230-00010
|View full text |Cite
|
Sign up to set email alerts
|

Acute HIV infection: impact on the spread of HIV and transmission of drug resistance

Abstract: Phylogenetic and epidemiological analyses underline the impact of PHI in the spread of HIV. Moreover, this study indicates that drug resistance transmission may have decreased recently in Switzerland through the increased frequency of infection with HIV non-B subtypes and the steady increase of patients with undetectable viraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 27 publications
7
151
1
8
Order By: Relevance
“…We have assumed that unlike human immunodeficiency virus (HIV) (Yerly et al, 2001), where viral loads are highest, acute HCV infection is not more infectious than chronic stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have assumed that unlike human immunodeficiency virus (HIV) (Yerly et al, 2001), where viral loads are highest, acute HCV infection is not more infectious than chronic stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of related virus are often interpreted as epidemiologically linked. For example, clusters of acute HIV infections may represent short transmission chains between high-risk individuals (Yerly et al 2001;Hue et al 2005;Pao et al 2005;Goodreau 2006;Brenner et al 2007;Drumright and Frost 2008;Lewis et al 2008). Because our model reproduces the moments of the cluster size distribution, it can be used to predict the level of clustering as a function of epidemiological conditions.…”
mentioning
confidence: 99%
“…Surveillance studies have demonstrated that approximately 10 to 20% of recently infected patients carry drug-resistant strains of HIV-1 (74,101,157,183). In addition, approximately 8 to 10% of drug-resistant isolates are identified in treatment-naive, chronically infected patients (178).…”
Section: Transmission Efficiencymentioning
confidence: 99%